Occupational obstructive airway diseases: How can early diagnosis be made to avoid chronic courses? - Frei-Stuber, Ludwig; Drexler, Hans; Heutelbeck, Astrid; Nowak, Dennis (Pneumologie, 2023)
Since abolishing the obligation to terminate the harmful professional activity from January 1st, 2021 onwards for some occupational diseases including obstructive respiratory diseases in Germany, the recognition of occupational diseases coded under 4301, 4302 and 1315 according the Occupational Diseases Ordinance has increased significantly. By the time these diseasese are recognized, they are usually already at an advanced stage. Therefore, early detection will play a greater role in the future, as the statutory accident insurance can offer individual preventive measures in order to minimize the consequences of illness and thus also the socio-economic burden. However, precursors of such obstructive airway diseases are often overlooked. For optimizing early detection, the statutory accident insurance worked out an early notification procedure for the respiratory tract - comparable to the already well-established dermatological procedure. "Early cases" from the pilot regions can be reported there; to qualify for being reported as early cases, patients must persue insured professional activity with potential effects on the respiratory tract and suffer from a disease of the upper or lower respiratory tract according to the ICD-10 code (e.g. J31.0 chronic rhinitis).
CRIS-Team WoS Importer:2023-05-12